Ação de antissépticos frente a biofilmes formado por microcosmo em superfície de titânio - Verardi, Georgia (2014)
Bacterial colonization around the implants leads to the development of mucositis or peri-implantitis and consequent loss of osseointegrated implant. The aim of this study was to evaluate the effect of four antiseptics facing microcosm biofilm formed by titanium surfaces. Biofilms were formed in 24 microwell plates on titanium disks with different surfaces (smooth - SL, smooth and treated with acid attack - SLAAC, sandblasted - SJ, sandblasted and treated with acid attack - SJAAc) from the saliva of a volunteer patient with periodontal disease. It was used for the bacterial culture device supplemented with mucin (DMM). Biofilms were grown anaerobically at 37 ° C for 48 h. After this period samples of each surface condition (n = 9) were treated individually by immersion for 1 min in antiseptic substances (chlorhexidine - CLX, chloramine T - TC, triclosan - TRI oils or essences - OE) and saline solution for negative control. The results were obtained by quantification of micro-organisms on blood agar plates after the treatments, tests and ANOVA and Tukey were used for statistical analysis. SJ, SJAAc and SL groups showed higher values of total and statistically similar micro-organisms, SLAAC got the smallest count value and statistically similar to SL. The SS group had a higher count value than OE and CT, there was no statistical difference between the antiseptic chemicals. Different antiseptics reduce the bacterial count around implants, there is significant difference between the titanium surfaces and antiseptic products, although no statistical significance was found for the interaction between these factors